Regional Seismic Studies in Central Asia - Priestley, Keith (1992)
Section A describes the preliminary analysis of the 2400 km long western Norilsk-Lake Baikal deep seismic sounding profile. Seismograms for the three nuclear explosions have been digitized, corrected for gain changes, and record sections constructed. These data have been compared with travel times predicted from several existing velocity models for Eurasia and modelling the data has begun. Section B describes a study of the tectonics of the South Caspian region. Earthquake mechanisms show overthrusting of the South Caspian basin from the north, west, and south. The combined effect will lead to the eventual destruction of the South Caspian basin and the possible formation of an intermediate depth seismic zone within the continental interior similar to the Hindu Kush.